Penerapan Model Project Based Learning Berbantuan Microsoft Excel Dalam Meningkatkan Kemampuan Analisis dan Penulisan Jurnal Ilmiah Mahasiswa pada Mata Kuliah Analisis Numerik - Widyaningrum, Ismi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Numerical Analysis is a course that plays an important role in training students' analytical thinking skills. The use of technology such as Microsoft Excel in learning numerical analysis can help students understand the calculation process more accurately, systematically, and efficiently. Based on the results of initial observations on students of the Mathematics Education Study Program at STKIP Syekh Manshur who attended the Numerical Analysis course, as many as 14 students were observed. The approach used is a quantitative approach, with the Pre-Experimental Design method in the form of a One-Group Pretest-Posttest Design. In the initial observation stage, it was found that students' ability in using Microsoft Excel was still low, resulting in a lack of students' ability to write scientific journals that depend on the results of numerical analysis. In the next stage, with the application of the Project-Based Learning model, it was found that there was a significant difference (Sig. < 0.05), so that H₀ was rejected and H₁ was accepted. These results indicate that the application of the PjBL model is effective in improving students' analytical and scientific journal writing skills in the Numerical Analysis course.